Phytochemical Phytochemical Compounds and Antihyperglycemic Activities from Beverage Composed Pluchea indica Less-Black Tea-Honey - Paini Sri Widyawati; Liza Frebriana (Food Science and Technology Journal (Foodscitech), 2023)
Pluchea indica Less has been developed into tea bag because it contains a number of phytochemical compounds, such as lignin, terpenes, benzoids, phenylpropanoids, alkanes, saponins, catechins, alkaloids, tannins, sterols, phenolhydroquinones, and flavonoids, which have been shown to have several biological activities, such as antioxidants, anti-inflammatory, anticholesterol, and antihyperglycemic. In its development, pluchea tea can be combined with black tea to produce certain functional values. Consumption of pluchea-black tea in daily life can be done with the addition of lemon or honey to increase antihyperglycemic activity. However, this study focused on determining the profile of phytochemical compounds and antihyperglycemic activity of pluchea-black tea honey drink. The research design used was a Randomized Block Design (RAK) with one factor including honey concentration consisting of six treatment levels: 0, 1, 2, 3, 4 and 5% (v/v). Each treatment was repeated four times. Parameters carried out are the profile of phytochemical compounds and antihyperglycemic activity through in vitro analysis, namely the activity of inhibiting a-amylase and a-glucosidase enzymes. The results showed that the use of honey in the manufacture of pluchea-black tea had an effect on the profile of phytochemical compounds and antihyperglycemic activity. The use of honey with a concentration of 5% produced the highest antihyperglycemic activity, 73.21±3.57% for the ability to inhibit the alpha-amylase enzyme and 77.27±5.25% for the ability to inhibit the alpha-glucosidase enzyme, respectively